Safety and efficacy of the predictive low glucose management system in the prevention of hypoglycaemia: protocol for randomised controlled home trial to evaluate the Suspend before low function. Issue 4 (15th April 2016) - Abraham, M B; Nicholas, J A; Ly, T T; Roby, H C; Paramalingam, N; Fairchild, J; King, B R; Ambler, G R; Cameron, F; Davis, E A; Jones, T W
Abstract : Introduction: Innovations with sensor-augmented pump therapy (SAPT) to reduce hypoglycaemia in patients with type 1 diabetes are an ongoing area of research. The predictive low glucose management (PLGM) system incorporates continuous glucose sensor data into an algorithm and suspends basal insulin before the occurrence of hypoglycaemia. The system was evaluated in in-clinic studies, and has informed the parameters of a larger home trial to study its efficacy and safety in real life. Methods and analysis: The aim of this report is to describe the study design and outcome measures for the trial. This is a 6-month, multicentre, randomised controlled home trial to test the PLGM system in children and adolescents with type 1 diabetes. The system is available in the Medtronic MiniMed 640G pump as the 'Suspend before low' feature. Following a run-in period, participants are randomised to either the control arm with SAPT alone or the intervention arm with SAPT and Suspend before low. The primary aim of this study is to evaluate the time spent hypoglycaemic (sensor glucose <3.5 mmol/L) with and without the system. The secondary aims are to determine the number of hypoglycaemic events, the time spent hyperglycaemic, and to evaluate safety with ketosis and changes in glycated haemoglobin. The study also aims to assess the changes in counter-regulatory hormone responses to hypoglycaemia evaluated by a hyperinsulinaemic hypoglycaemic clamp in a subgroup of patients with impaired awareness. Validated questionnaires are used to measure the fear of hypoglycaemia and the impact on the quality of life to assess burden of the disease. Ethics and dissemination: Ethics committee permissions were gained from respective Institutional Review boards. The findings of the study will provide high quality evidence of the ability of the system in the prevention of hypoglycaemia in real life. Trial registration number: ACTRN12614000510640, Pre-results.